Reproductive Health Vulnerabilities among Women Living with Salinity: Evidence from Satkhira, Bangladesh - Azmira Bilkis (Journal of Social Science and Humanities, 2026)
This study examines how climate change–induced salinity intrusion shapes women’s reproductive health vulnerabilities in coastal Bangladesh, focusing on Satkhira District. Using a convergent mixed-methods design, quantitative data were collected from 175 women and analyzed through logistic regression, while qualitative insights were generated from in-depth interviews and focus group discussions to capture lived experiences and contextual dynamics. The findings reveal a significant association between saline water exposure and adverse reproductive health outcomes, including reproductive tract infections (RTIs), menstrual irregularities, and gestational hypertension. Nevertheless, these outcomes are not driven by environmental exposure alone. Instead, they emerge through the interaction of freshwater scarcity, limited healthcare access, and gendered barriers to care-seeking. Qualitative evidence demonstrates how saline water use becomes embedded in everyday practices—particularly menstrual hygiene management (MHM)—transforming routine behaviors into pathways of chronic health risk. This study substantially advances climate-health scholarship by extending the Socio-Ecological Model. It identifies embodied practices, especially MHM, as critical mediating mechanisms linking environmental exposure to biological outcomes. It also advances the Gender and Climate Change Framework by demonstrating that vulnerability is differentiated across income, education, and intra-household power relations. Overall, the study highlights that reproductive health vulnerabilities in salinity-affected regions are co-produced through environmental stressors, gendered practices, and structural inequalities. It calls for integrated, gender-responsive interventions that combine sustainable freshwater provision, accessible reproductive healthcare, and efforts to address underlying social constraints in climate-vulnerable coastal settings.